Solar photocatalytic asphalt for removal of vehicular NOx: A feasibility study. (1st September 2018) - Fan, Wenguang; Chan, Ka Yan; Zhang, Chengxu; Zhang, Kai; Ning, Zhi; Leung, Michael K.H.
Highlights: Photocatalytic asphalt can effectively perform NOx removal. Solar radiation can activate the C-TiO2 loaded asphalt. Optimal loading was found for the best performance. Abstract: Solar radiation can be used to activate photocatalyst for direct functional photocatalytic applications. In the present research, solar photocatalytic asphalt was developed for removal of vehicular nitrogen oxides (NOx ) to mitigate the roadside air pollution problem. Visible-light activated photocatalytic asphalt was fabricated by embedding carbon-modified titanium dioxide (C-TiO2 ) onto asphalt surface under proper heat treatment. Material characterizations were conducted to study the surface and light absorption properties. Chamber tests of NOx removal were conducted under the conditions that simulated the ambient environment under sunlight. The experimental results show that NOx removal by C-TiO2 photocatalytic asphalt is viable, and is better than the more commonly used P25. The parametric analysis also reveals that the material fabrication process can be optimized to make photocatalytic asphalt that is highly effective, durable and cost-effective. Field tests were carried out to reveal the feasibility and evaluate the durability of the photocatalytic coating. This study demonstrates successful use of solar radiation via photocatalysis for functional application that can solve environmental problems.